Irish political prisoners / [3] 1960-2000 : braiding rage and sorrow / Seán McConville - McConville, Seán (Irish political prisoners, 2021)
"This is a comprehensive, detailed and humane account of the thousands who came into custody during the years of the Northern Ireland conflict and how they lived out the months, years and decades in Irish and English maximum security prisons. Based on extensive archival research and numerous interviews, it provides an account of riots, escapes, strip and dirty protests and hunger strikes. The final part of a trilogy dealing with Irish political prisoners from 1848 to 2000 by renowned expert Seán McConville, this is an essential resource for students and scholars of Irish history and Irish political prisoners; it is also a major contribution to the study of imprisonment"--